Cooperative localization algorithm based on time-ofarrival in wireless senor network - Qianqian LU; Youming LI; Shengming CHANG; Nana LI (Dianxin kexue)
A novel cooperative location method based on time-of-arrival in wireless senor networks was proposed. Firstly, the optimization problem for the target location was established. Secondly, the mixed semi-positive definite and second-order cone relaxation techniques were used to convert the original non-convex problem into a convex optimization problem. In this way, a fast suboptimal solution to the original problem was obtained. Finally, computer simulations show that the proposed method has lower root mean square error (RMSE) which is closer to the Cramer-Rao lower bound (CRB).